2006
DOI: 10.1159/000093379
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Course of Progressive Multiple Sclerosis in Brazilian Patients

Abstract: Objective: To describe the clinical course and outcome of multiple sclerosis with progressive onset in Brazilian patients. A total of 238 medical records were reviewed, 26 cases (10.9%) fulfilled Thompson criteria (2000), and 5.80% classified as primary progressive and 5.04% relapsing progressive according to Lublin and Reingold. Study Population: 19 Caucasians and 7 non-Caucasians; male:female ratio 1.2:1, mean age at onset was 34 ± 7.9 years. Results: Non-Caucasian patients had earlier onset of disease. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 66 publications
0
8
0
1
Order By: Relevance
“…However, during the last 10 years, various case studies have shown that, despite the low prevalence of the disease, the hot climate and racial miscigenation, this illness now appears with clinical manifestations similar to those observed in Western countries [24][25][26] .…”
Section: Resultsmentioning
confidence: 99%
“…However, during the last 10 years, various case studies have shown that, despite the low prevalence of the disease, the hot climate and racial miscigenation, this illness now appears with clinical manifestations similar to those observed in Western countries [24][25][26] .…”
Section: Resultsmentioning
confidence: 99%
“…The RRMS form affects more women than men, between 20 and 40 years of age. It is characterized by non systematic neurological syndromes, suggesting disseminated inflammatory lesions in the CNS; while the progressive course of multiple sclerosis affects both men and women above 40 years of age 20,21 leading to an insidious and growing motor and sensitive dysfunction on lower limbs -in most of the cases -related to spinal cord commitment 22,23 . Those clinical differences were previously associated to a reduced inflammatory load detected in brain scans of PPMS patients versus the ones with the RRMS form.…”
Section: Discussionmentioning
confidence: 99%
“…Demographic and clinical data were obtained from medical records and from the SIAPEM database [26]. Twenty-six cases had been described in a previous study [5]. Further cases were identified and also followed up by one of the authors (CCVF).…”
Section: Patient Selectionmentioning
confidence: 99%
“…Multiple sclerosis (MS) that is primarily progressive at onset is the second most frequent MS phenotype in Caucasian patients of the northern hemisphere [1], and according to Lublin and Reingold [2] may have two subtypes: primary progressive multiple sclerosis (PPMS), observed in 7-15% of patients, who experience a gradual progression of disability from the onset of disease with no exacerbations; and progressive-relapsing multiple sclerosis (PRMS), which occurs in fewer than 5% and in whom the initial progressive course is later accompanied by one or more relapses [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation